Shifting from ‘AI Solutions’ to ‘AI Coloniality’: Resignification of Artificial Intelligence and Digital Apartheid - Warganegara, Muhd Rafli Ramadhan (Institute of International Studies, 2024)
The study explores the evolving role of Artificial Intelligence (AI) beyond its perceived neutrality, delving into its politicization particularly in the Global South's digitalization context. It argues that once seen as a neutral problem-solving tool, AI has transformed into a politically charged entity, embodying biases rooted in its creation and training processes. This transformation marks a shift towards AI colonialism, where corporate interests intertwine with extensive data extraction practices, raising concerns about extractive colonial power dynamics. The discourse of AI colonialism underscores the interdependence of AI, corporate interests, and the extraction of meaning, prompting a re-evaluation of regulatory frameworks to mitigate profit-driven activities. Furthermore, the article examines how AI's intersection with data extraction facilitates societal surveillance, leading to Digital Apartheid in Sub-Saharan Africa—a manifestation of racial capitalism in the digital age. This Digital Apartheid perpetuates social segregation based on race through AI-driven technologies, exacerbating biases that disproportionately affect people of color. The article advocates for open discussions on digital and AI ethics to address these challenges to counteract racial discrimination and foster a more inclusive and equitable technological landscape. Overall, the abstract highlights the complex socio-political dimensions of AI, urging for proactive measures to mitigate its negative impacts and ensure fair and just technological development.Keywords: artificial intelligence; AI coloniality; digital apartheid; racial capitalism